Efektifitas Hasil Belajar Passing Bawah Permainan Bola Voli dengan Metode Example Non-Example - Ilyas Hidayat; Ilham Arvan Junaidi; Hengki Kumbara (Journal on Education, 2023)
This study aims to determine the effective example non-example learning model for class XI student learning outcomes at SMA Negeri 11 Palembang in carrying out underhand passing in a volleyball game. The method used in this study is the experimental research method. The type of research used in this research is Pre-Experimental Design. Using the design form "One-Group Pretest-Postest Design", in this study there were pretest and posttest, so that the effect of treatment can be calculated by comparing the values ​​of pretest and posttest. In the study, samples were taken from class XI MIPA 3, totaling 32 students. The initial test results obtained 24 students with low scores and 8 students with high scores. After being given treatment (example non-example), students experienced an increase, namely 26 students with high scores and 6 students with moderate grades. the average result of the student's initial test (pretest) was 46.45 and the average result of the student's final test (posttest) was 78.33. Because there has been an increase after being given treatment (treatment) compared to before being given treatment (treatment). In testing the hypothesis, the tcount<ttable value was obtained, namely 22.410<1.729, so that it can be concluded that there is an effectiveness of class XI IPA 3 student learning outcomes at SMA Negeri 11 Palembang City in passing under volleyball games through the non-example example method.